The relationship between neurocognition and side-step cutting biomechanics in women's Australian football players - Rolley, T. L.; Saunders, N.; Hendy, A.; Major, B.; Goodwill, A.; Shultz, S.; Fox, A. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
Despite increased awareness and targeted efforts, anterior cruciate ligament (ACL) injuries continue to frequently occur within the women`s Australian-rules football league (AFLW). AFLW ACL injuries frequently occur when performing a defensive side-step cut. Considering the reactive nature of this scenario, neurocognitive function may be an important risk factor. Therefore, the purpose of this study was to investigate the relationship between neurocognition and side-step cutting biomechanics in women`s Australian football players. Relationships between neurocognitive measures and 3D knee loads during unanticipated side-stepping were examined. No statistically significant relationships were found. These findings provide recommendations for future research to explore different cognitive parameters and ensure sufficient cognitive demand in the testing environment.